Implementasi Sinkronisasi Waktu Antar Bluetooth Low Energy Device menggunakan Metode Timing-Sync Protocol for Sensor Network - Muhammad Fachri Hasibuan; Agung Setia Budi; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Technological developments encourage the use of wireless networks and Wireless Sensor Network systems more and more. However, The problem with Wireless Network technology is the time difference between one node and another, on WSN each node communicates with the same frequency but has different local times, therefore there is a need for time synchronization. Time synchronization is a method for synchronizing the time on nodes on a network. There are several types of time synchronization, but this research focuses on the Timing-sync Protocol for Sensor Network (TPSN) method which is implemented over a wireless network using Bluetooth Low Energy (BLE) communication. The advantages of Bluetooth Low Energy are low power usage and efficiency, data transmission speeds of up to 1Mb / s and the potential for technology that continues to grow. This research using 3 BLE nodes which divided into 1 Server and 2 clients. This system uses ESP 32 as a microcontroller for data processing and Real Time Clock (RTC) as a timer for each nodes. The server node functions as a data exchange, and as the root node. The client node will request a request for synchronization to the server and the server will provide its local time as the reference time. From the implementation results, the error test data was obtained 30 times with the results of an average error value of 10.36 ms and synchronization testing as well as computation time was obtained 10 times with an average value of accuracy offset of 2.65 ms and Propagation Delay 16.85 ms, the computational average value is 102.3ms.